Pelaksanaan Fisioterapi pada Kasus Bell’s Palsy di RS PKU Muhammadiyah Selogiri - Ramadhani, Jihan Nabila; Wahyu Rizkika Azis; Lintang Cahya Ningrum; Arif Pristianto; Arif Abdullah (Lembaga Pengembangan Kinerja Dosen, 2025)
Bell's Palsy is a sudden onset of peripheral facial nerve paralysis that is generally unilateral. This condition is characterized by facial muscle weakness, asymmetry, difficulty closing the eyes, and facial expression disorders. Associated risk factors include exposure to cold temperatures and the habit of chewing ice cubes, which can trigger vasospasm of the blood vessels and inflammation of the facial nerve. Physiotherapy management is important to accelerate recovery, prevent complications such as synkinesis and contractures, and improve the patient's quality of life. This study aims to describe the implementation of physiotherapy in cases of Bell's Palsy at PKU Muhammadiyah Selogiri Hospital and evaluate the effectiveness of physiotherapy intervention on the recovery of facial function in patients. A case report was conducted on a 41-year-old female patient diagnosed with right-sided Bell's Palsy. The examination included anamnesis, static and dynamic inspection, palpation, basic movement examination, sensory examination, and assessment using the House-Brackmann Facial Grading System (HBGS). Physiotherapy interventions were given three times a week, including Infra Red (IR), Transcutaneous Electrical Nerve Stimulation (TENS), light massage, facial exercises (raising eyebrows, closing eyes, blowing, smiling), and education on preventing exposure to cold. Evaluation was performed using Manual Muscle Testing (MMT) and Ugo Fisch. The implementation of physiotherapy with a combination of IR, TENS, massage, and facial exercises is effective in gradually improving the facial function of patients with Bell's Palsy. Physiotherapy also plays a role in educating patients about the prevention of recurrence related to environmental risk factors and lifestyle.